2022
DOI: 10.7440/res81.2022.03
|View full text |Cite
|
Sign up to set email alerts
|

La reconstrucción de la identidad musulmana de las jóvenes de ascendencia marroquí con estudios superiores en Cataluña

Abstract: Resumen | El presente artículo tiene por objetivo analizar cómo las hijas de familias marroquíes residentes en Cataluña resignifican su identidad como jóvenes musulmanas y catalanas, a partir de mostrar su propia (re)construcción de la musulmaneidad. Ello debido a la tendencia a identificar a las personas "musulmanas" y "lo musulmán" como paradigma de "lo irreductible", lo cual sustenta discursos y representaciones sociales monolíticas y estáticas que devienen en formas de discriminación y exclusión con mayor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…According to the authors, recognizing linguistic diversities helps students gain agency, develop self-esteem correlated to their presence in the university, and empower their identities in the contemporary multilingual reality. In the same line, Parella, Contreras, and Pàmies' [31] research on Muslim student girls of Moroccan descent in Catalonia found that higher education helps students to not develop assimilationist identity experiences, leading to an increase in the agency capacity of young university students.…”
Section: Students Belonging To Minority Groups And/or Having Migrated...mentioning
confidence: 90%
See 1 more Smart Citation
“…According to the authors, recognizing linguistic diversities helps students gain agency, develop self-esteem correlated to their presence in the university, and empower their identities in the contemporary multilingual reality. In the same line, Parella, Contreras, and Pàmies' [31] research on Muslim student girls of Moroccan descent in Catalonia found that higher education helps students to not develop assimilationist identity experiences, leading to an increase in the agency capacity of young university students.…”
Section: Students Belonging To Minority Groups And/or Having Migrated...mentioning
confidence: 90%
“…In the case of research on minority and/or migrant groups at the university level, however, we find limited research and minimal diversity in the topics addressed, even though multicultural diversity has also been visible at these educational levels for some time [10,31]. The few existing publications in Spain mainly address the limitations and conditions of access to institutions of higher education [32][33][34][35], and to a lesser extent, the possible scenarios of successful academic trajectories and favorable entry to the university [36].…”
Section: Students Belonging To Minority Groups And/or Having Migrated...mentioning
confidence: 99%